A History of the Sociology of Mental Health Section - Magee, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This Account of the development of the section is based on interviews with the four persons who were primarily responsible for founding the section: Carol Aneshensel, Bill Avison, Jay turner and Blair Wheaton .